Factors influencing nurses’ pain assessment and management of road traffic casualties: a qualitative study at a military hospital in Ghana - Tata, T.K.; Ohene, L.A.; Dzansi, G.A.; Aziato, L. (BMC Emergency Medicine, 2024)
Background Evidence shows that patients who visit the surgical and trauma emergency units may be discharged with untreated or increased pain levels. This study explored nurses’ pain assessment and management approaches at a trauma-surgical emergency unit in Ghana. Methods Seventeen nurses who work in the trauma department participated in this qualitative exploratory descriptive study. In-depth individual interviews were conducted, and the thematic analysis was utilized to identify emerging themes and subthemes. Results Three main themes were identified: patient pain indicators, pain management, and institutional factors influencing pain management. The study revealed that nurses rely on verbal expressions, non-verbal cues, physiological changes, and the severity of pain communicated. The findings highlighted staff shortage, inadequate resources, and lack of standardized guidelines as factors affecting pain and management. Conclusions Although the study offers critical new perspectives on nurses’ experiences regarding pain related issues at the trauma-surgical emergency units, its small sample size limited its generalizability.
Research Article
Keywords: Trauma; Emergency unit; Pain assessment